Structural insights into DNA-stabilized silver clusters12. Issue 21 (16th May 2019) - Schultz, Danielle; Brinson, Robert G.; Sari, Nese; Fagan, Jeffrey A.; Bergonzo, Christina; Lin, Nancy J.; Dunkers, Joy P.
Abstract : Sedimentation profiles shows that purified AgDNA nanoclusters exist in both extended (major peak) and compact (minor peak) morphologies. Abstract : Despite their great promise as fluorescent biological probes and sensors, the structure and dynamics of Ag complexes derived from single stranded DNA (ssDNA) are less understood than their double stranded counterparts. In this work, we seek new insights into the structure of single Ag N ssDNA clusters using analytical ultracentrifugation (AUC), nuclear magnetic resonance spectroscopy, infrared spectroscopy and molecular dynamics simulations (MD) of a fluorescent (Ag N ssDNA) 8+ nanocluster. The results suggest that the purified (Ag N ssDNA) 8+ nanocluster is a mixture of predominantly Ag15 and Ag16 species that prefer two distinct long-lived conformational states: one extended, the other approaching spherical. However, the ssDNA strands within these clusters are highly mobile. Ag(i ) interacts preferentially with the nucleobase rather than the phosphate backbone, causing a restructuring of the DNA strand relative to the bare DNA. Infrared spectroscopy and MD simulations of (Ag N ssDNA) 8+ and model nucleic acid homopolymers suggest that Ag(i ) has a higher affinity for cytosine over guanine bases, little interaction with adenine, and virtually none with thymine. Ag(i ) shows a tendency to interact with cytosine N3 and O2 and guanine N7 and O6, opening the possibility for a Ag(i )–base bifurcated bond to act as a nanocluster nucleation and strand stabilizing site. This work provides valuable insight into nanocluster structure and dynamics which drive stability and optical properties, and additional studies using these types of characterization techniques are important for the rational design of single stranded AgDNA nanocluster sensors.